Effect of Different Iodine Concentrations on Patient-Reported Discomfort in Contrast-Enhanced Computed Tomography: A Prospective Comparative Trial - Vahldiek, Janis Lucas; Schaafs, Lars-Arne; Niehues, Birgit K.; Hamm, Bernd; Niehues, Stefan Markus (RöFo - Fortschritte auf dem Gebiet der Röntgenstrahlen und der bildgebenden Verfahren, 2020)
Purpose Reducing contrast media injection speed while maintaining iodine flux is a promising workaround to lower or avoid contrast media-related discomfort during CT examinations. This approach demands contrast media with a higher concentration to guarantee excellent image quality. It remains unclear whether these concentration changes affect the patient’s experience. Thus, the aim of this study was to evaluate the influence of different concentrations of intravenous iodinated contrast media on patient discomfort during and after contrast media delivery.Materials and Methods Patients were randomized to receive either Iomeprol 400 mg/ml (group A) or 300 mg/ml (group B) during routinely scheduled CT examinations at our department. The iodine delivery rate and injection time were kept constant in both groups. After examination, study subjects completed a digital questionnaire on different CM-related sensation items using digital visual analogue scales.Results 253 consecutive patients were enrolled in a 6-month period. Most of the patients reported heat sensation in both groups (mean VAS: 5.3 mm in group A vs. 5.0 mm in group B, p = 0.5). Taste sensation also did not differ significantly between both groups (2.4 mm vs. 2.0 mm, p = 0.08). Pain sensation was reported to be significantly lower in group B patients (1.3 mm vs. 1.0 mm, p = 0.005), even though pain sensation in general was reported on a very low level. Other injection-related sensations were rarely reported.Conclusion Patient-reported discomfort during intravenous injection of high-concentration contrast media (400 mg/ml) was low and only marginally different when compared to the injection of contrast media with a lower concentration. The injection of highly concentrated contrast media showed comparable overall patient acceptance, allowing a reduction of the injection speed and volume during examinations.Key Points: Citation Format
Keywords: adults; contrast media; iodine; computed tomography; high-concentration contrast media